Development and Validity of Western University's On-Road Assessment. (January 2017) - Classen, Sherrilene; Krasniuk, Sarah; Alvarez, Liliana; Monahan, Miriam; Morrow, Sarah A.; Danter, Tim
Although used across North America, many on-road studies do not explicitly document the content and metrics of on-road courses and accompanying assessments. This article discusses the development of the University of Western Ontario's on-road course, and elucidates the validity of its accompanying on-road assessment. We identified main components for developing an on-road course and used measurement theory to establish face, content, and initial construct validity . Five adult volunteer drivers and 30 drivers with multiple sclerosis participated in the study. The road course had face and content validity, representing 100% of roadway components determined through a content validity matrix and index. The known-groups method showed that debilitated drivers (vs. not debilitated), made more driving errors ( W = 463.50, p = .03), and failed the on-road course, indicating preliminary construct validity of the on-road assessment. This research guides and empirically supports a process for developing a road course and its assessment.